Superheating field in superconductors with nanostructured surfaces - Pathirana, W. P. M. R.; Gurevich, A. (Frontiers in Electronic Materials, 2023)
We report calculations of a DC superheating field Hsh in superconductors with nanostructured surfaces. Numerical simulations of the Ginzburg–Landau (GL) equations were performed for a superconductor with an inhomogeneous impurity concentration, a thin superconducting layer on top of another superconductor, and superconductor–insulator–superconductor (S-I-S) multilayers. The superheating field was calculated taking into account the instability of the Meissner state with a non-zero wavelength along the surface, which is essential for the realistic values of the GL parameter κ. Simulations were performed for the material parameters of Nb and Nb3Sn at different values of κ and the mean free paths. We show that the impurity concentration profile at the surface and thicknesses of S-I-S multilayers can be optimized to enhance Hsh above the bulk superheating fields of both Nb and Nb3Sn. For example, an S-I-S structure with a 90-nm-thick Nb3Sn layer on Nb can boost the superheating field up to ≈500 mT, while protecting the superconducting radio-frequency (SRF) cavity from dendritic thermomagnetic avalanches caused by local penetration of vortices.